Love that story : observations from a gorgeously queer life - Van Ness, Jonathan (HarperOne, an imprint of HarperCollins Publishers, 2022)
In Jonathan Van Ness' New York Times bestselling memoir Over the Top, he showed readers how the incredibly difficult moments from his life (surviving sexual abuse and addiction, being diagnosed with HIV) have existed alongside great joy and positivity (landing a breakout role on Netflix's Queer Eye, becoming an amateur figure skater and professional stand-up comedian, doting on his cats). If Jonathan has learned anything from these experiences, it's that in order to thrive, he had to push past the shame and fear of being his true self. To embark on that journey, he had to get comfortable with being uncomfortable. In this candid and curious essay collection, Jonathan takes a thoughtful, in-depth look at timely topics through the lens of his own personal experience--instances that have required him to learn, grow, and back handspring layout to a better understanding of the world around him. He dives deeply and widely--from a poignant reflection on grief and embracing body neutrality to an examination of the HIV safety net and white privilege--to share the ways in which he has learned to embrace change. These stories speak to doing the work to challenge internalized beliefs, finding compassion and confidence, and learning more about what makes us all so messy and gorgeous. Balancing the dark and the light, the serious and the signature humor that is Jonathan Van Ness, these essays will encourage readers to examine their individual assumptions and expand their horizons. Ultimately, it is about giving ourselves the permission to be the flawed and fabulous humans we are, and loving our stories.